PENERAPAN MANAJEMEN PEMASARAN BERBASIS TEKNOLOGI INFORMASI PADA SEKTOR JASA DI KOTA SERANG - Sucihati, Sucihati; Fidziah, Fidziah; Bahits, Abdul (Yayasan Education and Social Center, 2024)
This research aims to examine the application of information technology-based marketing management in the service sector in Serang City, which plays an important role in the local economy. Even though information technology has great potential to increase marketing efficiency, challenges such as limited human resources (HR), technological infrastructure, and digital literacy are significant obstacles. Using a qualitative approach, data was collected through in-depth interviews with service businesses in Serang City. The research results show that although there is adoption of technology, especially social media for promotions, the application of more complex technologies such as big data analytics and marketing personalization is still limited. Apart from that, low digital literacy among business actors, especially MSMEs, hinders the optimization of information technology. This research suggests the need for training and development of human resources as well as government policies that better support technology development in the service sector, in order to increase competitiveness and expand market opportunities in Serang City.